METHOD OF MANUFACTURING NEEDLE-LIKE BODY, AND TRANSFER PLATE FOR NEEDLE-LIKE BODY - YAMADA YUMIKO (2013)
PROBLEM TO BE SOLVED: To provide a method of manufacturing a needle-like body using a transfer plate by which a needle-like body including holes in a plurality of needles can easily and precisely be transfer-molded and also which has durability.SOLUTION: The method of manufacturing a needle-lie body is a method of manufacturing a needle-like body 1 including a plurality of needles on the surface of a base section, and having holes provided in the needles by notching part of the slopes of the needles. The method of manufacturing the needle-like body includes a resin filling step, a transfer plate pressing step, and a release step. In the resin filling step, a resin is filled in the needle transfer plate 11 by using the needle transfer plate 11 and a base section transfer plate 12. In this case, the needle transfer plate includes: a contour section 11a for defining recess sections having a shape of reversed recesses and protrusions of the needle; and a protrusion section 11b having a shape of reversed recesses and protrusions of the needle, extending toward an opening section from the bottom surface of the recess section, and patially coming into contact with the contour section 11a. The base section transfer plate includes a plate-like section defining the bottom section of the base section. In the transfer plate pressing step, the resin remaining on the needle transfer plate 11 is brought into contact with the needle transfer plate 11 by pressing the base section transfer plate 12 to the resin. In the release step, the resin is taken out of the needle transfer plate 11 and the base section transfer plate 12.